(untitled) (Conference on English Language Teaching, 2023)
Machine translation has emerged as a vital tool for bridging language barriers in our increasingly interconnected world. This article provides a comprehensive analysis of the accuracy of two leading machine translation platforms: Google Translate and DeepL. The aim is to compare their translation accuracy, strengths, and weaknesses, enabling readers to make informed decisions when choosing the most suitable tool for their translation needs. It provides readers with valuable insights into the accuracy of Google Translate and DeepL, empowering them to make informed decisions when selecting a machine translation tool. Recommendations based on specific translation needs and use cases are offered, guiding users towards the most suitable platform for their requirements.